Understanding online communicative language features in social networking environment - Siti Hamin Stapa,; Azianura Hani Shaari, (Penerbit UKM, 2012)
This paper discusses the findings of a research study that seeks to investigate the language features and patterns of online communicative language amongst young Malaysian Facebook users. The acquisition of online literacy might create a gap or linguistic disparity that distinguish the young online users from the older generations who are not used to online communication environment hence, it is due to the same concern that led to the departure of this study. With the corpus of over 500,000 words of Online Communicative Language derived from a one year of Facebook conversations among 120 young Malaysians from different ethnic groups, mother tongues, and cultural background, it is hoped that the study will shed light into the new patterns of Online Communicative Language among young Malaysians that somehow signifies a reconstruction of an online identity among the young users; regardless of their cultural differences and backgrounds. Virtual Ethnography was employed, which involved daily observations and documentations of actual conversations on Facebook in a period of 12 months. Data were analyzed using Content Analysis in examining the features and patterns employed by the participants. The findings of the study suggest that the features used by these online users are spelling innovations and modifications, combinations of letter and number homophone, reduction or omission of vowels, replacement of <s> with <z>, the use of one letter to represent a word, the use of playful jargons, the used of acronyms and abbreviations and the use of emoticons. As a conclusion, language evolution is seen as an ongoing process and the development of online communicative language is always unpredictable even though it might originated from a re-thinking process of some old spelling conventions in media and not language that derived on its own.